Current Diagnosis and Treatment of Choledocholithiasis - Renaldi, Kaka; Firman, Fauzan Hertrisno (The Indonesian Society for Digestive Endoscopy, 2023)
The presence of gallstones in the common biliary duct is known as choledocholithiasis. Obstructive jaundice is the main clinical manifestation, which can cause acute cholangitis characterized by fever, jaundice, and right upper quadrant abdominal pain. The best diagnostic modality for choledocholithiasis is magnetic resonance cholangiopancreatography (MRCP). The treatment of choledocholithiasis involves extraction of gallstones using endoscopic retrograde cholangiopancreatography (ERCP), followed by stenting, and then cholecystectomy.